Utilization of Fermented Chicken Feather Flour Using Rhizopus sp in Feed on the Growth of Striped Catfish (Pangasianodon hypophthalmus) - Nazar, Muhammad Ahlun; Adelina, Adelina; Suharman, Indra (Fakultas Perikanan dan Kelautan Universitas Riau, 2024)
This study aims to determine the effect of feeding containing fermented chicken feather flour on feed efficiency and growth of striped catfish fry. The test fish used weighted 2.85 ± 0.33 g. The containers used for observing fish growth were 15 units of floating net cages made of gauze measuring 1x1x1 m with a stocking density of 25 ind/m3 and 5 units of aquariums measuring 60x35x40 cm as containers for observing the digestibility of feed with a stocking density of 25 ind/m3. This research method used a one-factor Completely Randomized Design (CRD) with five treatment levels and three replications. The treatments in this study were P0 (feed without fermented feather meal), P1 (feed containing 7.5% fermented feather meal), P2 (feed containing 15% fermented feather meal), P3 (feed containing 22.5% flour fermented chicken feathers), and P4 (feed containing 30% fermented chicken feather flour). The test feed protein was about 40%. The amount of feed given is 5% of the body weight of the fish with a frequency of 3 times a day, namely morning, afternoon, and evening. Fish rearing was carried out for 56 days. Measure the digestibility of feed by giving feed containing an indicator of 0.5% chromium oxide (Cr2O3). Feed is offered three times a day, namely morning, afternoon, and evening, as much as 5% of the body weight of the fish. The feces excreted by the fish are then collected and dried. The collected feces were analyzed for protein content and Cr2O3 to obtain feed and protein digestibility data. The results of this study indicated that the best treatment was P3 (feed containing 22.5% fermented chicken feather meal), resulting in feed digestibility of 55.36%, protein digestibility of 85.39%, feed efficiency of 83.59%, protein retention of 36.33%, specific growth rate of 3.38%, and survival of 92.00%.